2011
DOI: 10.1071/mf10145
|View full text |Cite
|
Sign up to set email alerts
|

Does more maternal investment mean a larger brain? Evolutionary relationships between reproductive mode and brain size in chondrichthyans

Abstract: Abstract. Chondrichthyans have the most diverse array of reproductive strategies of any vertebrate group, ranging from egg-laying to live-bearing with placental matrotrophy. Matrotrophy is defined as additional maternal provisioning beyond the yolk to the developing neonate; in chondrichthyans, this occurs through a range of mechanisms including uterine milk, oophagy, uterine cannibalism and placentotrophy. Chondrichthyans also exhibit a wide range of relative brain sizes and highly diverse patterns of brain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 57 publications
(105 reference statements)
4
27
0
Order By: Relevance
“…4(b)] were slightly lower than those reported when using species as independent data points [Fig. 4(a)], indicating that previous estimates have been biased by phylogenetic contrasts, although they were comparable to those values published for chondrichthyans that were similarly independent of phylogeny ( α = 0·38, n = 37, Yopak et al , 2007; α = 0·37, n = 57, Yopak & Montgomery, 2008; α = 0·353, α RMA = 0·39, Yopak & Frank, 2009; α RMA = 0·46, α RMA = 0·41, Mull et al , 2011).…”
Section: Brain Scalingsupporting
confidence: 73%
“…4(b)] were slightly lower than those reported when using species as independent data points [Fig. 4(a)], indicating that previous estimates have been biased by phylogenetic contrasts, although they were comparable to those values published for chondrichthyans that were similarly independent of phylogeny ( α = 0·38, n = 37, Yopak et al , 2007; α = 0·37, n = 57, Yopak & Montgomery, 2008; α = 0·353, α RMA = 0·39, Yopak & Frank, 2009; α RMA = 0·46, α RMA = 0·41, Mull et al , 2011).…”
Section: Brain Scalingsupporting
confidence: 73%
“…Ellis and Otway (2011) unveiled new details of the environment in which the embryos of wobbegong sharks develop. Mull et al (2011) revealed one possible advantage of investing in live young -matrotrophic sharks have brains that are 20-70% larger than those of similar-sized leicithotrophic species. These types of discoveries are important because they can have other societal benefits, including development of new materials, biomedical discoveries, understanding of other biological processes, and can also help change the public's understanding of sharks (and hence their receptiveness to conservation management that may affect them).…”
Section: Priority Setting and Communicationmentioning
confidence: 99%
“…This is evidenced by the fact that 38% of the papers published from 'Sharks Down Under Conference' in 1991 (Pepperell 1992) were related to life history, whereas life history-related papers account for only 24% of those published in the current conference volume. The types of research that are needed include reproductive biology (Ainsley et al 2011;Graham and Daley 2011;Mull et al 2011), age and growth (Tanaka 2011) and mortality (Simpfendorfer et al 2005). In particular, research targeted at endangered species (e.g.…”
Section: Biological Dimensionsmentioning
confidence: 99%
“…Much of the variation in brain organization in these fishes is attributed to differences in telencephalon size and the size and degree of folding (or foliation) of the cerebellum . Hypertrophy of these brain areas is associated with various ecological niche and life-history factors, such as habitat, lifestyle, feeding behavior, and reproductive mode [Northcutt, 1978;Graeber, 1984;Yopak et al, 2007;Lisney et al, 2008;Mull et al, 2011]. In comparison, very little is known about interspecific variation in the organization of other brain areas, such as the midbrain or mesencephalon.…”
Section: Introductionmentioning
confidence: 99%